Analysis of Impregnation Mechanism of Weft-Knitted Commingled Yarn Composites by Staged Consolidation and Laboratory X-Ray Computed Tomography - Ayadi, Abderrahmane; Deléglise-Lagardère, Mylène; Park, Chung Hae; Krawczak, Patricia (Frontiers in Materials, 2019)
Absorption-based microcomputed tomography (µCT) scans using polychromatic X-ray sources are frequently used to analyse the microstructure of polymer-matrix composites. Assuming the proportionality between linear X-ray attenuation coefficients and grey levels in the reconstructed µCT images, segmentation techniques can be used to conduct qualitative and quantitative analyses. Nevertheless, the reliability of such analyses is limited in partially consolidated composites formed of commingled yarns due to low contrast induced by beam hardening and partial volume effect. This paper aims at investigating the possibility of using low-contrast µCT images to analyse fibre bed deformation and impregnation mechanism by staged consolidation of a weft-knitted fabric of commingled thermoplastic/glass yarns. The experimental work is focused on the effect of the compaction ratio of the consolidation cycle. Absorption-based µCT analyses are conducted for representative samples using a voxel size of 10 µm and a constant energy-level of the X-rays source. Preliminary qualitative analyses of the raw reconstructed images indicate that beam hardening is the most significant in the case of the non-consolidated sample and that partial volume effect makes it difficult to visually distinguish between dry and impregnated zones inside the yarns at a compaction ratio of 63%. Thus, two image-quality descriptors, viz. contrast and signal-to-noise ratio are evaluated based on the K-means clustering method to follow their variation for four consolidation levels. The corresponding volume fractions of glass fibres, thermoplastic matrix and voids are compared with the results of a second weight-controlled thresholding method. Considering that the weight-controlled thresholding method is less sensitive to beam hardening, it is confirmed that obtaining reliable segmentation results based on the K-means method requires a contrast around 0.5 and signal-to-noise ratio lower than 3. The results from the comparison with the classical consolidation scenario of commingled yarns confirm the potential of using µCT images of different qualities to characterize partially consolidated weft-knitted fabrics.